2015
DOI: 10.1016/j.stem.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 Inhibition Specifically Targets Inv(16) Acute Myeloid Leukemic Stem Cells by Restoring p53 Acetylation

Abstract: Summary Acute myeloid leukemia (AML) is driven and sustained by leukemia stem cells (LSCs) with unlimited self-renewal capacity and resistance to chemotherapy. Mutation in the TP53 tumor suppressor is relatively rare in de novo AML; however, p53 can be regulated through post-translational mechanisms. Here, we show that p53 activity is inhibited in inv(16)+ AML LSCs via interactions with the CBFβ-SMMHC (CM) fusion protein and histone deacetylase 8 (HDAC8). HDAC8 aberrantly deacetylates p53 and promotes LSC tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 47 publications
(55 reference statements)
5
79
2
1
Order By: Relevance
“…A recent study showed that HDAC8 is also responsible for the deacetylation of p53. In inv(16)ϩ leukemia cells, inhibition of p53 deacetylation reactivated p53, and induced apoptosis (28). It is possible that the cell cycle delay and growth arrest we observed in MCF7 cells is also mediated by altered p53 acetylation rather than solely from accumulated ac-SMC3.…”
Section: Hdac8 Inhibition Does Not Mimic Cohesin Depletion In Mcf7mentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study showed that HDAC8 is also responsible for the deacetylation of p53. In inv(16)ϩ leukemia cells, inhibition of p53 deacetylation reactivated p53, and induced apoptosis (28). It is possible that the cell cycle delay and growth arrest we observed in MCF7 cells is also mediated by altered p53 acetylation rather than solely from accumulated ac-SMC3.…”
Section: Hdac8 Inhibition Does Not Mimic Cohesin Depletion In Mcf7mentioning
confidence: 85%
“…In addition to ac-SMC3, acetylated p53 is a target of HDAC8. In inv(16)ϩ AML, chemical inhibition of HDAC8 prevented p53 deacetylation, leading to restoration of p53-induced apoptosis of leukemia-initiating cells (28).…”
mentioning
confidence: 99%
“…LSCs rely on oncogenic signals that inactivate the p53 pathway, and reactivation of dormant p53 in LICs can be a selective strategy to eradicate LICs (8083). Our data suggest that targeting of MDMX with a dual MDMX/MDM2 inhibitor is a strategy to target LICs in AML.…”
Section: Discussionmentioning
confidence: 99%
“…77 p53 deacetylation is also triggered by the CBFb-SMMHC FP of inv (16)/t(16;16) AML, which complexes with HDAC8 and p53, thus promoting p53 deacetylation. 78 Additionally, the CBFb-SMMHC/ Runx1 oligomers mislocalize HIPK2 (p53 activator) into cytoplasmic filamentous structures, hence interfering with p53 apoptotic function. 79 The favorable prognosis of this AML and of APL might be explained in part by the presence of a relatively higher TAp73/DNp73 ratio, compensating for wtp53 dysfunction.…”
Section: Aml With Chromosomal Translocationsmentioning
confidence: 99%